Graphene deposited liquid crystal and thermal sensitivity using photonic crystals. (25th January 2021) - Elsayed, Hussein A; Sayed, Fatma A; Aly, Arafa H
Abstract: In this work, we present a simple design to act as a temperature sensor based on the well-known one dimensional photonic crystal. The main idea of the proposed sensor is essentially depending on the inclusion a defect layer of graphene monolayers deposited on nematic liquid crystal through the photonic crystal. The transfers matrix method, Kubo-Formula, and fitting experimental data represent the core axes of our theoretical treatment. Here, our design is prepared to sense temperature based on the shift of the resonant peak with the temperature variation. The performance of such sensor is demonstrated by calculating the sensitivity, figure of merit, detection limit, sensor resolution and the quality factor. The effect of the thickness of the defect layer and the mode of polarization as well on the performance of our sensor is investigated. The numerical results show that our sensor could be of interest in many fields of application due to the high values of its sensitivity and quality factor. The proposed sensor could provide a sensitivity of 4 nm °C −1 and quality factor up to 11000.